Phonon limited electronic transport in Pb. (1st August 2017) - Rittweger, F; Hinsche, N F; Mertig, I
Abstract: We present a fully ab initio based scheme to compute electronic transport properties, i.e. the electrical conductivity σ and thermopower S, in the presence of electron–phonon interaction. We explicitly investigate the k -dependent structure of the Éliashberg spectral function, the coupling strength, the linewidth and the relaxation time τ . We obtain a state-dependent τ and show its necessity to reproduce the increased thermopower for temperatures below the Debye temperature, without accounting for the phonon-drag effect. Despite the detailed investigations of various k - and q -dependencies, the presented scheme can be easily applied to more complicated systems.